Grande sonate pour le piano dédiée à Mr. Joseph de Sonnenfels, par L.v. Beethoven. Oeuvre 28 .. - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Paris; S. Richault; France, 2023)
Early edition of the Piano Sonata no. 15 in D major, op. 28, published in Paris by S. Richault.